Clinical and Associated Immunological Manifestations of HFMD Caused by Different Viral Infections in Children. (27th May 2016) - Wang, Jingjing; Pu, Jing; Liu, Longding; Che, Yanchun; Liao, Yun; Wang, Lichun; Guo, Lei; Feng, Min; Liang, Yan; Fan, Shengtao; Cai, Lukui; Zhang, Ying; et al.
Hand, foot, and mouth disease (HFMD), with vesiculae on the hands, feet and mouth, is an infectious disease caused by many viral pathogens. However, the differences of immune response induced by these pathogens are unclear. We compared the clinical manifestations and the levels of immunologic indicators from 60 HFMD patients caused by different viral pathogens to analyze the differences in the immune response. It was shown that Th2 cytokines (IL-4 and IL-10) increased significantly in EV71-infected children; Th1 cytokines (IL-2 and IFN-γ) rose in CA16-infected children; both Th1 and Th2 cytokines elevated in non-EVG-infected children; only individual cytokines (such as IL-10) went up in EVG-infected children. Meanwhile, the antibodies induced by viral infection could not cross-interfere between the different pathogens. These differences might be due to variations in the immune response induced by the individual pathogens or to the pathogenesis of the infections by the individual pathogens.